Investigating the influencers of materialism in adolescence - Marcelo de Rezende Pinto; Alisson Oliveira Mota; Ramon Silva Leite; Ricardo César Alves (Tourism & Management Studies, 2017)
This article presents results of a research whose objective was to identify the influential attributes in the level of materialism among adolescents in Brazil. The review of the literature contemplated discussions about the materialism among adolescents that culminated in the proposition of a theoretical model to be tested empirically. The model was composed of three influencer variables of materialism (age, economic class, gender) and by seven influencer constructs (communication with friends, communication with parents, effect of peers, media exposure, attitudes to adverts, attraction of celebrities and self-esteem). Fieldwork involved 1,353 adolescents between the ages of 11 and 18 from public and private schools at elementary and middle school level. For the analysis of the data the structural equation modeling was used. Among the results, it can be emphasized that the major influencers of the level of materialism among adolescen